The Influence of Macroeconomic on Investment Performance - Muhammad Firmansyah; Immanuel Mu'ammal; Arini Roro Anggun Tsalasa (Economics Development Analysis Journal, 2024)
Shocks caused by macroeconomic variables and monetary transmission have impacted investment portfolios in the five ASEAN countries, both in the short and long term. This research aims to evaluate each country's proficiency in managing macroeconomic variables in relation to portfolio investments. Additionally, it seeks to explore the influence of these macroeconomic variables on portfolio investment and the time required for their effects to manifest in both short-term and long-term contexts. This study is quantitative in nature and uses secondary data. The data were sourced from the central banks of the ASEAN-5 countries and from investing.com for stock price index information. The results indicate that interest rates, exchange rates, and stock price indexes significantly affect portfolio investment in the short term. In contrast, in the long term, inflation, exchange rates, and money supply were found to have a significant impact on portfolio investment. Based on these findings, it is recommended that ASEAN-5 governments focus on exchange rates and economic openness, as these factors influence portfolio investment in the region and can attract investors' interest